Numerical Study of the Thermo-Mechanical Behavior of Steel–Timber Structures Exposed to Fire - Saavedra-Flores, E; Yanez-Cart, S; Guzman-Inostroza, C; Pina, J; Godoy-Dellepiani, M (Elsevier Ltd, 2023)
The latest trends in the construction industry related to sustainable buildings, has driven the use of timber as a construction material. One example is the continuous increase of timber structural elements made of Cross-Laminated Timber (CLT) walls and floors. In this context, Steel–Timber Composite (STC) floors, composed of CLT slabs and steel beams, represent a new alternative to traditional floor systems. Some advantages of STC structures are a reduction of the building mass and better thermal insulation, among others. Despite these benefits, the response of timber structures under a fire scenario remains a consistent concern. To address this issue, in this paper the thermo-mechanical response of STC structures exposed to fire is investigated. To this end, a one way coupled Computational Fluid Dynamics (CFD) and Finite Element Method (FEM) approach was employed. The software Fire Dynamics Simulator (FDS) was used for the CFD fire analyses and ANSYS for the FEM transient heat transfer and thermo-mechanical analyses. Three different STC floor structural configurations, having similar pre-fire performance, were proposed to assess their response when subjected to a given fire scenario. A representative room of a residential building was defined to simulate an accidental fire scenario to which the STC floor structures were exposed. The material properties and fire features were adopted in accordance with the Eurocode Standard and recent investigations found in the literature. The results indicated that after a 30 min fire exposure the CLT slabs showed a 25 mm thick charred layer on their exposed surface. Furthermore, compression failure was identified in the CLT slab upper fibres. Regarding to the steel beams, local buckling, and fracture in the area next to the end supports was observed. Overall, STC structures with closed cross sections steel beams showed a better fire performance than those that included open cross sections such as I-shaped ones. © 2022 Elsevier Ltd